Mitochondrial Dna Methylation: A Possible Breach In Pathophysiology Of Cardiovascular Diseases (Applied Biological Research, 2023)
Cardiovascular diseases (CVD) are a cluster of diseases that hamper cardio vascular system and may lead to death. Several injuries and risk factors like  obesity correspond to the malfunctioning of heart and blood vessels that lead to  the condition of stroke, myocardial infarction, deep vein thrombosis (DVT), etc.  Only a few studies have depicted the role of mitochondrial genes and their  epigenetic regulation in DVT. The association of certain mitochondrial genes of  electron transport chain and oxidative phosphorylation has been reported in  Expression of these genes is regulated by DNA methylation. Obesity not  only influences the CVD but also has been found responsible for alteration in  mtDNA methylation. In present study, of the 5182 research articles, only 13 and  4 papers were found dealing with the qualitative and quantitative analysis,  respectively. MT-CO1, MT-CO2, MT-CO3, MT-TL1 and PPARGC1 genes were  noted to be involved in disease condition. The mitochondrial DNA methylation  has profound impact on mitochondrial gene expression which may lead to the  development of dysfunctional mitochondria and cause the development of  various cardiovascular diseases. In present paper, a systemic analysis was done  with the hypothesis that mitochondrial DNA methylation has an intriguing role  in the occurrence of several CVDs in relation to obesity.
Keywords: Cardiovascular diseases; patho-physiology; methylation; mitochondrial DNA